2010
DOI: 10.1073/pnas.0913985107
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a gain-of-function FGFR2 Crouzon mutation provides evidence of loss of function activity in the etiology of cleft palate

Abstract: Cleft palate is a common birth defect in humans and is a common phenotype associated with syndromic mutations in fibroblast growth factor receptor 2 (Fgfr2). Cleft palate occurred in nearly all mice homozygous for the Crouzon syndrome mutation C342Y in the mesenchymal splice form of Fgfr2. Mutant embryos showed delayed palate elevation, stage-specific biphasic changes in palate mesenchymal proliferation, and reduced levels of mesenchymal glycosaminoglycans (GAGs). Reduced levels of feedback regulators of FGF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 42 publications
5
66
1
Order By: Relevance
“…Brinkley and Vickerman showed that reducing HA in palatal mesenchyme through pharmacological enhancement of its degradation inhibited palatal shelf elevation in organ culture as well as in vivo (Brinkley and Vickerman, 1982). A palatal shelf elevation defect in mice homozygous for the Fgfr2 C342Y missense mutation was also associated with reduced HA accumulation in the palatal mesenchyme (Snyder-Warwick et al, 2010). We found that Golgb1 mutant embryos exhibit reduced HA accumulation and concomitantly increased cell density in the palatal mesenchyme by E13.5.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Brinkley and Vickerman showed that reducing HA in palatal mesenchyme through pharmacological enhancement of its degradation inhibited palatal shelf elevation in organ culture as well as in vivo (Brinkley and Vickerman, 1982). A palatal shelf elevation defect in mice homozygous for the Fgfr2 C342Y missense mutation was also associated with reduced HA accumulation in the palatal mesenchyme (Snyder-Warwick et al, 2010). We found that Golgb1 mutant embryos exhibit reduced HA accumulation and concomitantly increased cell density in the palatal mesenchyme by E13.5.…”
Section: Discussionmentioning
confidence: 55%
“…We found that mouse embryos deficient in Golgb1 consistently exhibit failure of palatal shelf elevation. Although failure of palatal shelf elevation has been described in several other mutant mouse strains (Jiang et al, 1998;Jin et al, 2010;Lan et al, 2004;Matsumura et al, 2011;Snyder-Warwick et al, 2010;Yu et al, 2010), the molecular and cellular mechanisms regulating palate shelf elevation are still not well understood (Bush and Jiang, 2012;Ferguson, 1988). It has been proposed that an intrinsic force is progressively generated to drive palatal shelf elevation and the chief component of this intrinsic force appears to be regionally specific accumulation of extracellular GAGs, predominantly HA (Ferguson, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that during early chicken and mouse facial development, FGF receptor-1 (FGFR1) and at lower levels also FGF receptor-2 (FGFR2) are widely expressed in the facial mesenchyme (Bachler and Neubü ser, 2001;Firnberg and Neubü ser, 2002). Mice deficient in Fgfr1 develop facial and palatal clefts with incomplete penetrance, and all embryos lacking Fgfr1 and Fgfr2 in the palatal mesenchyme develop a cleft secondary palate, suggesting that these two receptors might function partially redundantly in transducing FGF signals to the facial mesenchyme (Snyder-Warwick et al, 2010;Trokovic et al, 2003). Whether Tbx22 expression is affected in Fgfr1/Fgfr2 double mutants, however, has so far not been analyzed.…”
Section: Fgf and Bmp Signaling Pathways Converge On The Regulation Ofmentioning
confidence: 99%
“…Embryos bearing the Fgfr2C342Y mutant show delayed palate elevation and reduced levels of mesenchymal GAGs. Reduced levels of feedback regulators of FGF signaling suggest that this gain-offunction mutation in FGFR2 ultimately resembles loss of FGF function in the palate mesenchyme (15). Future work to characterize GAG compositions in Fgfr1 cKO palate shelves is needed to assess the possibility that loss of Fgfr1 in CNC-derived mesenchymal cells changes GAG compositions and impairs palate shelf elevation required for palate shelf fusion.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FGF signaling intensity during palatogenesis is delicately balanced. Expression of a constitutively active FGFR2 mutant in the epithelium increases palatal shelf mesenchyme proliferation and delays elevation of the shelves, resulting in cleft palate and other craniofacial disorders (15,16). Disruption of Sprouty 2 (Spry2), a negative feedback regulator of FGF signaling pathways, results in abnormal palate formation (17).…”
mentioning
confidence: 99%